PAST BEHAVIOUR, FINANCIAL LITERACY, AND INVESTMENT DECISION-MAKING PROCESS OF INDIVIDUAL INVESTORS - Nuury Nurmelia; Firstina Nur Fadilla; Nur Wahyuni AR; Farah Margaretha Leon (SIMAK, 2022)
This study is a quantitative study that aims to determine the influence of past behavior, financial literacy, and investment decision-making processes on individual investor. The object in this study was an individual investor listed on the Indonesia Stock Exchange. The samples in this study were selected using purposive sampling techniques. There are 148 samples of investors domiciled in the Jabodetabek area. Primary data is obtained through answers from questionnaires distributed to individual investors and measured using scale of likert. Data is processed using AMOS software and research methods using SEM test analysis. The results showed that individual attitudes, behavioral control and capital market training influence the intention to invest. Financial literacy affects individual attitudes and behavioral control. While subjective norms and past behavior have no influence on the intention to invest in the capital market. This research has implications for securities companies, the Indonesia Stock Exchange, as well as issuers of public companies, and for investors.